Sex-Specific Influence of the SCARB1 Rs5888 SNP on the Serum Lipid Response to Atorvastatin in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention - Wu DF; Lin D; Lu F; Liao QC; Wu YJ; Wang Z; Yu K; Li WJ; Deng JL (Dove Medical Press, 2020)
Dong-Feng Wu,1,* Dan Lin,2,* Feng Lu,1 Qin-Chen Liao,1 Yu-Juan Wu,1 Zhou Wang,1 Kun Yu,1 Wei-Jun Li,1 Jin-Long Deng1 1Department of the Geriatric Cardiology, People’s Hospital of Guangxi Zhuang Autonomous Region, Nanning 530021, Guangxi, People’s Republic of China; 2Department of the First Comprehensive Clinic, The Affiliated Stomatology Hospital of Guangxi Medical University, Nanning 530021, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jin-Long Deng Department of the Geriatric CardiologyPeople’s Hospital of Guangxi Zhuang Autonomous Region, 6 Taoyuan Road, Nanning 530021, Guangxi, People’s Republic of ChinaEmail djl_gx@163.comBackground: Epidemiological studies have shown that there are sex differences in blood lipid levels and lipid responses to statins. Previous studies have shown that the rs5888 single nucleotide polymorphism (SNP) in the scavenger receptor class B type 1 (SCARB1) gene is associated with serum lipid levels in a sex-specific manner. The present study was undertaken to detect the sex-specific influence of the SCARB1 rs5888 SNP on the serum lipid response to atorvastatin in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI).Methods: A total of 158 unrelated ACS patients (108 males, 50 females) were enrolled, and all patients received atorvastatin 20 mg/daily after PCI. Genotyping of the rs5888 SNP was performed by polymerase chain reaction and direct sequencing. Serum lipid profiles were determined before treatment and after an average follow-up time of one year.Results: The baseline serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and apolipoprotein (Apo)AI levels were higher in females than in males (P< 0.05). After treatment with atorvastatin, serum TC, LDL-C, and ApoB were decreased, and ApoAI was increased (P< 0.05). The effects of atorvastatin on serum lipid levels were different between males and females, and females had greater decreases in TC, LDL-C and ApoB levels than males (P< 0.05). The genotypic frequencies of the rs5888 SNP were not different between males and females. The atorvastatin response was not associated with the rs5888 SNP in males (P > 0.05). Nonetheless, in female individuals carrying the rs5888 T-allele, we observed a greater reduction in TC, LDL-C, and ApoB levels after the use of 20 mg/day atorvastatin (P< 0.05).Conclusion: This study indicates that the SCARB1 rs5888 T-allele was associated with a greater reduction in serum TC, LDL-C, and ApoB after atorvastatin treatment in female patients with ACS undergoing PCI.Keywords: sex-specific, lipid, atorvastatin, scavenger receptor class B type 1, polymorphism, coronary artery disease